Evaluation of the role of Kurdish women in the poems of Mullah Khalil Mashakhti - Ahmed, Asst.Prof.Dr.Dolt Mohammed (Sulaimani Journal for Humanities, 2026)
Poetry as a human activity has taken effective steps at any stage and is always the amount of human actions, opinions and thoughts in society, in such a way that the history, content and purpose of each text Literature carries the message and social, economic, political and cultural situation of its time Other activities in human life have shown that Mullah Khalil Mashakhti, like all other poets, paid great attention to women and their problems and encouraged women to achieve a happy life One of the ways to solve the problems of society in general is to evaluate the role of women in society by describing their work, activities and values These poems reflect the lifestyle and social personality of Kurdish women in various ways and characteristics. Social criticism in general is one of those theories that pays great attention to the personality of women as social self in particular and the social dimension of man is worthy of attention. Therefore, the principles of this theory are reflected in the poems of Mullah Khalil Mashakhti. We chose this book as the raw material for our research entitled “Evaluation of the Role of Kurdish Women in the Poems of Mullah Khalil Mashkhti”. He conducted his research according to the critical method.
Keywords: Poetry; Social Problems; Lifes Self; Title; Woman